DAMARWULAN Digital analytics & marketing automation for resilient waterfront urban leisure advancement Innovation to strengthen east java’s marine tourism performance - Santoso, Rudi; Koentjoro, Edo Yonatan; Amalia (Edelweiss Applied Science and Technology, 2025)
Digital transformation has become a key driver in increasing the competitiveness of tourist destinations, especially in urban coastal areas that face environmental pressures and tourist behavior dynamics. This research aims to develop and test the concept of DAMARWULAN (Digital Analytics & Marketing Automation for Resilient Waterfront Urban Leisure Advancement) as a technology-based strategic innovation to strengthen the performance of marine tourism destinations in East Java. The research approach used a mixed-method, with a combination of quantitative (survey of 267 tourists) and qualitative (in-depth interviews with 12 stakeholders). The results show that the integration of digital analytics allows destination managers to understand traveler behavior in real-time, while marketing automation contributes to increased visitor engagement and loyalty. The DAMARWULAN system has also been proven to support the resilience of coastal destinations through the provision of environmental data, risk management, and strengthening service adaptation capacity. In addition, this innovation encourages the redefinition of marine tourism as part of a smart and connected urban lifestyle (smart urban leisure). The theoretical implications of the research strengthen the synergy between digital marketing theory, sustainable destination management, and urban ecotourism development. Practically, the DAMARWULAN model can be a strategic framework that is applicable to local governments, tourism actors, and local communities in increasing the competitiveness of technology-based marine tourism. Recommendations were given for system trials through pilot projects in leading destinations in East Java.